ELECTRIC BIKES FOR GREEN MOBILITY IMPROVEMENT IN GILI IYANG, MADURA - Nugraha, Yoga Uta; Mubarok, Muhammad Syahril; Apsari, Retna (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This community service program is implemented in an island region that has limited access to electricity and fuel. This program is implemented on Gili Iyang Island, Sumenep, Madura. On the island, the only mode of transportation available is motorbikes and three-wheeled motorbikes due to limited and narrow roads. The price of gasoline reaches two to four times the normal price. Based on these conditions, the issue raised in this community service program is the use of electric bicycles for mobility, with the hope that it can also be a means of supporting the main tourist attraction of the island known as "Oxygen Island". This program is training for the community on how to assemble and maintain electric bicycles. The electric bicycles used in this program are designed with compact and flexible advantages, equipped with lithium batteries with a range of up to 30 km. In addition, there is a pedal assist feature to make it easier to pedal when needed, such as when going uphill or crossing sandy roads. For recharging electric bicycles, a solar shelter is provided, which helps save transportation costs. Training is provided through theoretical and practical materials. Participants can directly implement the theory that has been conveyed when practicing assembling bicycles. Based on the results of the pre and post tests, in general, there was an increase of 17-50% in the knowledge and skills of participants related to the assembly and maintenance of electric bicycles. This is a very strong belief that the Gili Iyang community has been able to use and maintain electric bicycles.